Absence of Host-Specific Genes in Canine and Human Staphylococcus pseudintermedius as Inferred from Comparative Genomics - Alice Wegener; Els M. Broens; Linda van der Graaf-van Bloois; Aldert L. Zomer; Caroline E. Visser; Jan van Zeijl; Coby van der Meer; Johannes G. Kusters; Alex W. Friedrich; Greetje A. Kampinga; Gregorius J. Sips; Leonard Smeets; et al. (MDPI AG, 2021)
Staphylococcus pseudintermedius is an important pathogen in dogs that occasionally causes infections in humans as an opportunistic pathogen of elderly and immunocompromised people. This study compared the genomic relatedness and antimicrobial resistance genes using genome-wide association study (GWAS) to examine host association of canine and human S. pseudintermedius isolates. Canine (n = 25) and human (n = 32) methicillin-susceptible S. pseudintermedius (MSSP) isolates showed a high level of genetic diversity with an overrepresentation of clonal complex CC241 in human isolates. This clonal complex was associated with carriage of a plasmid containing a bacteriocin with cytotoxic properties, a CRISPR-cas domain and a pRE25-like mobile element containing five antimicrobial resistance genes. Multi-drug resistance (MDR) was predicted in 13 (41%) of human isolates and 14 (56%) of canine isolates. CC241 represented 54% of predicted MDR isolates from humans and 21% of predicted MDR canine isolates. While it had previously been suggested that certain host-specific genes were present the current GWAS analysis did not identify any genes that were significantly associated with human or canine isolates. In conclusion, this is the first genomic study showing that MSSP is genetically diverse in both hosts and that multidrug resistance is important in dog and human-associated S. pseudintermedius isolates.